Recovery of Biosurfactant Using Different Extraction Solvent by Rhizospheric Bacteria Isolated from Rice-husk and Poultry Waste Biochar Amended Soil. Issue 1 (1st January 2020) - Adebajo, S. O.; Akintokun, P. O.; Ojo, A. E.; Akintokun, A.K.; Badmos, O.A.
ABSTRACT: Biochar is a stable solid material made from biomass via pyrolysis and can endure in soil for thousands of years. The present study aimed to evaluate the potential of rhizospheric microorganisms in rice-husk and poultry waste biochar-amended soil for biosurfactant production. Rhizospheric microorganisms in biochar-amended soil were isolated and screened for biosurfactant production using different screening methods. Potential rhizospheric bacteria was used to produce biosurfactant using different recovery techniques and its hydrocarbon degrading efficiency was determined. A total of 41 rhizospheric bacteria were recovered from biochar-amended soil. Pseudomonas and Bacillus spp were the dominant isolates. Pseudomonas putida showed best biosurfactant potential isolates from the different screening results and was used to produce biosurfactant. Chloroform-methanol showed good recovery solvent for biosurfactant extraction. Chloroform/methanol (2:1) gave the highest quantity (3.15 ± 0.26) g/L of biosurfactant while ethyl acetate produced the least yield of biosurfactant (1.13 ± 0.82) g/L. Pseudomonas putida also showed the potential to degrade hydrocarbon over a period of 10 days. The results obtained revealed that potential isolates for biosurfactant production and efficient hydrocarbon degraders could be recovered from rice-husk and poultry waste biochar-amended soil.